The salience of psychotic experiences: neural correlates in the general population - Neidhart, Maja; Henze, Gina-Isabelle; Vogel, Bob O; Mohnke, Sebastian; Banaschewski, Tobias; Walter, Henrik (Schizophrenia bulletin, 2025)
Psychotic experiences (PEs) frequently occur at a subclinical level in the general population, including symptoms like hallucination and delusion. An important hypothesis is the aberrant salience hypothesis, according to which the salience network (SN) plays a decisive role coordinating between inner and outer world, anchored in the dorsal anterior cingulate cortex (dACC) and anterior insula (AI). Given SN’s central role in PE development and maintenance, investigating its functional connectivity (FC) in a population-based sample is critical for understanding its etiology.Resting-state functional connectivity (rsFC) data from n = 84 of the general population were captured. Community Assessment of Psychic Experiences-Positive Scale (CAPE-15) quantified PE. rsFC-analyses were conducted with ENIGMA HALFpipe and FSL, performing seed-based correlation analysis of dACC and AI. We investigated the impact of PE on rsFC of the SN within group-level 1 sample t-tests with additional covariate (ie, PE) correcting for age and sex. rsFC maps were converted using Fisher Z-transformation, false discovery rate correction was applied.With increasing PE, key SN-nodes (AI, dACC) showed significant hyperconnectivity (PFDR < .01) to other network structures like the default mode, central executive, visual, auditory, and ventral attention network (eg, thalamus, parahippocampal gyrus, frontal pole, lateral occipital cortex, planum temporale, inferior frontal gyrus).Our findings support the idea that the SN is crucial for the development and maintenance of PE, even in the general population. Highlighting the SN’s role in attributing salience to irrelevant stimuli through increased attention and the search for a subjective cognitive explanation.